Boosting Natural Killer Cell-Mediated Targeting of Sarcoma Through DNAM-1 and NKG2D - Sayitoglu, Ece Canan; Georgoudaki, Anna-Maria; Chrobok, Michael; Ozkazanc, Didem; Josey, Benjamin J.; Arif, Muhammad; Kusser, Kim; Hartman, Michelle; Chinn, Tamara M.; Potens, Renee; Pamukcu, Cevriye; Krueger, Robin; et al. (Frontiers in Immunology, 2020)
Sarcomas are malignancies of mesenchymal origin that occur in bone and soft tissues. Many are chemo- and radiotherapy resistant, thus conventional treatments fail to increase overall survival. Natural Killer (NK) cells exert anti-tumor activity upon detection of a complex array of tumor ligands, but this has not been thoroughly explored in the context of sarcoma immunotherapy. In this study, we investigated the NK cell receptor/ligand immune profile of primary human sarcoma explants. Analysis of tumors from 32 sarcoma patients identified the proliferative marker PCNA and DNAM-1 ligands CD112 and/or CD155 as commonly expressed antigens that could be efficiently targeted by GM NK cells. Despite the strong expression of CD112 and CD155 on sarcoma cells, characterization of freshly dissociated sarcomas revealed a general decrease in tumor-infiltrating NK cells compared to the periphery, suggesting a defect in the endogenous NK cell response. We also applied a functional screening approach to identify relevant NK cell receptor/ligand interactions that induce efficient anti-tumor responses using a panel NK-92 cell lines genetically modified (GM) to over-express 12 different activating receptors. Using GM NK-92 cells against primary sarcoma explants (n=12) revealed that DNAM-1 over-expression on NK-92 cells led to efficient degranulation against all tested explants (n=12). Additionally, NKG2D over-expression showed enhanced responses against 10 out of 12 explants. These results show that DNAM-1+ or NKG2D+ GM NK-92 cells may be an efficient approach in targeting sarcomas. The degranulation capacity of GM NK-92 cell lines was also tested against various established tumor cell lines, including neuroblastoma, Schwannoma, melanoma, myeloma, leukemia, prostate, pancreatic, colon, and lung cancer. Enhanced degranulation of DNAM-1+ or NKG2D+ GM NK-92 cells was observed against the majority of tumor cell lines tested. In conclusion, DNAM-1 or NKG2D over-expression elicited a dynamic increase in NK cell degranulation against all sarcoma explants and cancer cell lines tested, including those that failed to induce a notable response in WT NK-92 cells. These results support the broad therapeutic potential of DNAM-1+ or NKG2D+ GM NK-92 cells and GM human NK cells for the treatment of sarcomas and other malignancies.